Information Technology Utilization in Fashion Industry - R D Santy; F Alfiana (International Journal of Research and Applied Technology (INJURATECH), 2021)
The purpose of this study is to dicover the needs of identification in a business and design that uses e-commerce design in the fashion field. In e-commerce systems, there are key functional features of information that can provide satisfaction to consumers. This study used descriptive qualitative methods, which are methods that can be interpreted as stages of problem solving, which describes a situation in the subject or object in this study. Transaction activities between sellers and buyers are included in the form of trade in using online media that can save consumers' time in shopping. The results of this study were the facts to help reach wider customers than offline stores, and finding a market gap for businesses and products. With the existence of e-commerce applications in the development of this fashion consumers can obtain a product at a cheaper and practical price to get the desired fashion mode.